Deranged hematological profile in patients presenting with malarial parasitaemia - Haroon, Amber; Zameer, Huda; Naz, Aneeqa; Afzal, Sohaib; Ammar, Tooba; Zafar, Ifrah (International Journal Of Community Medicine And Public Health, 2021)
Background: Alterations in the hematological parameters are thought to have the capacity to act as an adjuvant tool in strengthening the suspicion of malaria, thereby prompting a more meticulous search for malaria parasites. Methods: 186 cases with malaria positive for immunochromatographic test (ICT) malaria presenting with fever ≥101 °F, confirmed on peripheral blood film, of 20-60 years were included. Patients with coagulopathy and bleeding disorders such as hemophilia, brain tumors, tuberculosis meningitis, viral or bacterial encephalitis and multiple sclerosis were excluded. Sample was taken to the laboratory, for routine investigations like ICT malaria and complete blood count (CBC) to diagnose anemia and low platelet count. Results: Patients of 20 to 60 years of age with mean 41.80±8.51. Out of 186 patients, 101 (54.30%) were male and 85 (45.70%) were female with 1:2:1 ratio. Mean duration of disease was 4.91±1.32 days. Frequency of derangement in hematological parameters was anemia in 27 (14.52%) patients and 142 (76.34%) with thrombocytopenia. 127 cases were of Plasmodium vivax and 59 cases were of Plasmodium falciparum. Patients were more anemic as disease period prolonged. Patients infected by Plasmodium vivax showed more tendencies towards anemia and reduction in platelet count as compare to Plasmodium falciparum. Conclusions: The frequency of derangement in hematological parameters i.e. anemia and low platelet count, among malarial patients is quite high and more cases were of Plasmodium vivax and it showed anemia and thrombocytopenia was more pronounced in Plasmodium vivax.